Teologia jako nauka sui generis. W kontekście teologii ks. Franciszka Dziaska - Kotkowska, Elżbieta (Poznańskie Studia Teologiczne, 2020)
Rev. Franciszek Dziasek, S.Th.D. was a lecturer of the Archbishop’s Seminary in Poznan from 1950 to 1964. In his lectures, Introduction to Theological Sciences, step by step he justifies claims of theology to be science in the university sense. From the reception of his lectures we learn that he was living with what he preached. In the integral view of the two realities, [theologian and his knowledge] we are shown a trait of theology wisdom, which shows its specificity as the queen of sciences. A Poznan lecturer argues that theology is a science in the ordinary sense of the word. It is also the science of sui generis, because it derives its data from a revelation that is credible in the community of the Church.